Parametric analysis and mitigation of Ferroresonance in ungrounded power transformers: Algeria power plant approach - Mohammed Boukaf; Saliha Boutora; Hamid Bentarzi (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Ferroresonance in ungrounded power transformers is extremely dangerous for electric systems, causing serious overvoltage, equipment damage, and system instability. Until now, there have been fewer quantitative, parametric analytical studies and verified mitigation methods for real power systems. Although there has been a qualitative study of Ferroresonance, few have provided rigorous parametric assessments and validated mitigation actions for modern power plants at utility scale. This work fills these gaps through in-depth parametric analysis of the so-measured and so-calculated values and a validation of zigzag transformer grounding for the Ras Djinet 1131 MW power plant, serving as a case study in Algeria. This paper establishes a nonlinear mathematical model that reflects transformer saturation characteristics, grading capacitance (Cg), shunt capacitance (Csh), and magnetization resistance (Rm), and implements it in MATLAB/Simulink. Fundamental and chaotic Ferroresonance modes are identified using parametric sweeps spectral analysis (FFT). Act two: Modeling and validating zigzag grounding transformer mitigation. The study finds Cg (0.5–7 µF) increases strengthen Ferroresonance overvoltage, while Csh (0.3_7µF) and Rm (1500–65860Ω) reduce it, offering a damping effect, reducing peak voltages. Spectral analysis reveals the fundamental mode (dominated by 50 Hz), the Quasi-Periodic Mode, and the chaotic mode (multiple frequency components). With a zero-sequence current path, a zigzag grounding implementation completely removes Ferroresonance in all tested cases.